KAJIAN RESPON PENAMBAHAN GERBONG WANITA PADA LRT PALEMBANG - Jolanda, Meiza; Agustini, Marice (Universitas Muhammadiyah Palembang, 2023)
LRT (Light Rail Transit) is a fast and efficient transportation mode option. Women are one of the LRT transportation users with various obstacles, such as the level of security, which often does not receive special attention. The demands on women's time limit their ability to increase income productivity, and isolate them. So in several public transportations, including the LRT, women-only carriages have been added so that female passengers feel safe. In the process of avoiding violence in public transportation, there is a plan to have special women's carriages on the Palembang LRT. This research is to see the response of Palembang LRT users to whether it is necessary to add special women's carriages to avoid violence that occurs on the Palembang LRT and also to see the performance conditions of the Palembang LRT as a choice of transportation mode for the community.